Optimization of Anemia Prevention Improvement Among Trimester II Pregnant Women Through Educational Videos at Salembaran Jaya Health Centre Tangerang Regency - Faradilla Puteri Rochayu; Retno Widowati; Putri Azzahroh (International Journal of Midwifery and Health Sciences, 2023)
Background: Anemia is a condition in which the number of red blood cells or the capacity of red blood cells to carry oxygen is insufficient to meet physiological needs. Anemia pregnant women are pregnant women with Hb levels <11.0 g/dl who are examined at the first visit (K1). Pregnant women with anemia have a higher risk of giving birth to babies with iron deficiency anemia which can last throughout the child's early years and inhibit the growth of the child's brain cells and other body cells, resulting in delayed growth and development. Purpose: To determine the average value and influence on the knowledge and attitudes of second trimester pregnant women before and after being given educational video counselling. Methods: This quasi-experimental study used a one group pretest-posttest design. The sample in the study was 58 pregnant women. The sampling technique used purposive sampling. The research instrument consists of a questionnaire about questions aimed at respondents regarding anemia causes, characteristics, impact, prevention, how to overcome, treatment, good habits to prevent anemia. Result: The results showed that there was a significant effect on the average value before and after being given educational video counselling to second trimester pregnant women at the Salembaran Jaya Health Center, Tangerang Regency. Conclusions: Health education for pregnant women is very important so that pregnant women are expected to participate in every counselling activity to increase knowledge and attitudes to prevent anemia. characteristics, impact, prevention, how to overcome, treatment, good habits to prevent anemia.